2012
DOI: 10.2146/ajhp110241
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and economic costs associated with postthrombotic syndrome

Abstract: Appropriate measures to decrease PTS-related burdens may include the prevention of DVT, clear diagnostic criteria for PTS, and an education campaign aimed at increased standardization in the management of DVT. Gaps in the current understanding of the risk factors, diagnostic criteria, preventive strategies, and even treatment modalities for PTS hamper the ability of clinicians to employ measures that could reduce the occurrence of this disorder and the associated morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
0
36
0
6
Order By: Relevance
“…Despite treatment, ≈10% to 20% of patients with DVT develop severe post-thrombotic syndrome, a chronic disorder that decreases quality of life and reduces the capacity to walk and to work. 80,81 In the most severe cases, patients with post-thrombotic syndrome can develop venous ulcers, which are slow to heal and costly for the healthcare system. 80,81 Heit et al 82 reported an incidence of venous ulcers of 1.8 per 1000 population per year.…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite treatment, ≈10% to 20% of patients with DVT develop severe post-thrombotic syndrome, a chronic disorder that decreases quality of life and reduces the capacity to walk and to work. 80,81 In the most severe cases, patients with post-thrombotic syndrome can develop venous ulcers, which are slow to heal and costly for the healthcare system. 80,81 Heit et al 82 reported an incidence of venous ulcers of 1.8 per 1000 population per year.…”
Section: 24mentioning
confidence: 99%
“…80,81 In the most severe cases, patients with post-thrombotic syndrome can develop venous ulcers, which are slow to heal and costly for the healthcare system. 80,81 Heit et al 82 reported an incidence of venous ulcers of 1.8 per 1000 population per year. PE is associated with chronic thromboembolic pulmonary hypertension in approximately 4% of patients.…”
Section: 24mentioning
confidence: 99%
“…Considering the fact that 30-50% of DVT patients will later develop PTS [4], one can approximate the incidence of PTS. In about 10-20% of the patients, a severe PTS develops, which manifests with permanent limb oedema, trophic changes of the skin and leg ulcers [5,6]. Post-thrombotic venous ulcers are usually hard to heal and their recurrence rate is extremely high (24-69% after 12 months) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term complications of proximal DVT include Postthrombotic Syndrome (PTS), which is characterized by chronic limb heaviness, pain, swelling, paraesthesia, pruritis and pigmentation changes [1,2]. PTS affects between 23-43% of patients and has been shown to have a significant negative impact on quality of life and a large economic burden on the wider community [3][4][5][6][7]. Early active treatment to remove thrombus has been shown to result in better outcomes, including lower rates of venous valve dysfunction [8], recurrent DVT [9] and PTS [10][11][12].…”
Section: Introductionmentioning
confidence: 99%